RADIOGRAPHIC AND CLINICAL ASSESSMENT OF TWO CANALS IN THE MAXILLARY SECOND PREMOLAR - Aslam, Naveed; Asif, Muhammad; Nadeem, Asif; Qureshi, Asim; Tayyaba, Saffa; Mahmood, Tariq (Journal of Ayub Medical College Abbottabad, 2021)
Background: The second premolar is one of the teeth which are crucial both aesthetically as well as functionally and one of the most commonly endodontically treated tooth. Aim of the study was to assess the number of canals in maxillary second premolar by clinical and radiographic evaluation in Pakistani sub population. It was a cross sectional study conducted in Endodontic Department of Rehmat Memorial Dental Teaching Hospital, Abbottabad, from January 2019 to January 2020. Method: One hundred and five patients were selected for the study, based on non-probability sampling technique. All patients were examined clinically by exploration of pulp chamber followed by intra oral peri-apical radiograph to verify the clinical exploration of canals. Result: One hundred and five patients (46 males (43.8%) and 59 females (56.2%)} were selected for the study. Out of total 105 patients 47 (44.8%) had one canal and 58 (55.2%) had two canals. Out of 46 males 25 (54.3%) had two canals and out of 59 females 33 (56.9%) had two canals. Statistical analysis showed no significant difference (p=0.1871) of canals arrangements between genders. Conclusion: Clinicians should be careful whenever doing root canal treatment of maxillary second premolars because of the extreme variability of the anatomy of those teeth, there is always risk of missing the second canal. Frequency of two canals was high, which is not age or gender dependant